Penerapan Desain dalam Feeds dan Reels Instagram Terhadap Antusiasme Penonton dalam Berdonasi - Putra, Aditya Nugraha; Romadhona, Mahimma (Jurnal Ilmiah Wahana Pendidikan, 2024)
On World of Design, Design is used to make a person knowing the acknowledge about design, sometimes it used to be a message or a conveys to the world, like this journal which was written to be a guide for people to spread kindness and to teach people which design is compatible to a message, so many people don’t be outguided with the wrong guide of design basic